Investigation of Drought Risk Using a Dynamic Optimization Framework in Regional Water Allocation Procedure With Different Streamflow Scenarios - Hong, Xu; Basirialmahjough, Mahdi; He, Yuan; Moudi, Mahdi (Frontiers in Environmental Science, 2022)
Recently, the water supply process has experienced serious challenges, because, with the intensification of ‎drought, the imbalance between available water resources and demand for water in different sectors has led ‎to increased system risk. Therefore, this study proposed an optimal dynamic framework under different ‎scenarios aimed at improving the drought risk of the water supply system. In this sense, given the negative ‎effects of drought on the water supply procedure, the degree of drought risk is analyzed and improved ‎according to system performance parameters. After examining the developed model by initial data collected ‎from a real case study of Hamoun wetland in Iran, the most sensitive parameters were included reliability ‎and vulnerability, which in this regard, the highest degree of drought risk is related to the agricultural and ‎industrial sectors due to the acquisition of less reliability and greater vulnerability. In addition, given the ‎final output, adaptation measures such as demand governance scheme and weight scenario analysis have ‎been developed in order to investigate the drought risk of the system in more detail.‎